Sermon on Matthew 25:1-12 - Jüngel, Eberhard (Toronto journal of theology, 2002)
Brothers and sisters in Christ! On this Reformation day, we celebrate the rediscovery of the gospel-the gospel without which the world was full of death and darkness, according to the judgment of Martin Luther. The gospel brings light into the world, into our world so manifestly marked by death. This light is a light which gives life, a light which illumines, a light which warms.